Kinetics and Mechanism of Slurry Phase Air Oxidation of Benzyl Alcohol over Zirconium Vanadate Catalyst - Kanungo Joshi, Shweta; Sohani, Neena; Khare, Savita; Prasad, Rajendra (Asian Journal of Chemistry, 2020)
The kinetics of slurry phase air oxidation of benzyl alcohol to benzaldehyde over zirconium vanadate catalyst is reported in this study. Initial rates for the formation of product were determined by varying the partial pressures of the reactants. The data collected were found to satisfy a rate law: R = [(k1PBk2Po)/(k1PB + k2Po)]. The study suggests that reaction follows a Mars-Van Krevelen type of redox mechanism.